Sharing responsibility : the history and future of protection from atrocities - Glanville, Luke (Human rights and crimes against humanity., 2021)
A look at the duty of nations to protect human rights beyond borders, why it has failed in practice, and what can be done about itThe idea that states share a responsibility to shield people everywhere from atrocities is presently under threat. Despite some early twenty-first century successes, including the 2005 United Nations endorsement of the Responsibility to Protect, the project has been placed into jeopardy due to catastrophes in such places as Syria, Myanmar, and Yemen; resurgent nationalism; and growing global antagonism. In Sharing Responsibility, Luke Glanville seeks to diagnose the current crisis in international protection by exploring its long and troubled history. With attention to ethics, law, and politics, he measures what possibilities remain for protecting people wherever they reside from atrocities, despite formidable challenges in the international arena. With a focus on Western natural law and the European society of states, Glanville shows that the history of the shared responsibility to protect is marked by courageous efforts, as well as troubling ties to Western imperialism, evasion, and abuse. The project of safeguarding vulnerable populations can undoubtedly devolve into blame shifting and hypocrisy, but can also spark effective burden sharing among nations. Glanville considers how states should support this responsibility, whether it can be coherently codified in law, the extent to which states have embraced their responsibilities, and what might lead them to do so more reliably in the future. Sharing Responsibility wrestles with how countries should care for imperiled people and how the ideal of the responsibility to protect might inspire just behavior in an imperfect and troubled world.